2019
DOI: 10.1177/0825859719827021
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Knowledge and Comfort Providing Palliative Care: A Survey of Pediatricians in Mexico

Abstract: Background: Lack of education and training in palliative care has been described to be one of the most important barriers to pediatric palliative care implementation. Objective: To examine what factors determine the degree of knowledge and level of comfort Mexican pediatricians have providing pediatric palliative care. Methods: A questionnaire that assessed palliative care concepts was developed and applied online to Mexican pediatricians, both generalists and specialists. Results: A total of 242 pediatricians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 33 publications
(35 reference statements)
3
24
1
6
Order By: Relevance
“…There are limited data on physician knowledge of palliative care in other resource-limited settings; however, these results are comparable to previous results finding that physicians had a mean score of 68%. 28 Respondent alignment with WHO guidance on palliative care integration varied greatly in our study both among individual participants (7%-100%) and by country (62%-81%). In a multiple regression analysis, independent predictors of higher WHO alignment included previous palliative care education, more experience with patient death, and country of practice.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…There are limited data on physician knowledge of palliative care in other resource-limited settings; however, these results are comparable to previous results finding that physicians had a mean score of 68%. 28 Respondent alignment with WHO guidance on palliative care integration varied greatly in our study both among individual participants (7%-100%) and by country (62%-81%). In a multiple regression analysis, independent predictors of higher WHO alignment included previous palliative care education, more experience with patient death, and country of practice.…”
Section: Discussionmentioning
confidence: 77%
“…Although those with palliative education felt less burdened, they did not report higher confidence in providing elements of palliative care, and this differs from the effects of palliative care education in other low-income settings. 28 This study clearly captures low exposure to formal palliative care training among physicians caring for children with cancer in Eurasia (19%), with the majority of the respondents (81%) having no prior palliative care education. This represents an urgent need to increase access to palliative care training for physicians treating children with cancer in the region.…”
Section: Discussionmentioning
confidence: 89%
“…These findings align with published data from other resource-limited settings that attributed delayed palliative care to physician attitudes, discomfort, and the need to control patient care. 13,14,27 However, contrary to physician perceptions of family unreadiness and resistance to palliative care consultation, children with cancer and their parents value and express interest in the early integration of palliative care in high-resource settings. 28 The limited data available from LMICs have illustrated that although parents resisted direct communication between the pediatric palliative care team and the patient, they valued increased information, communication, social support, and adequate pain management.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are corroborated by studies in other resource-limited settings in which financial and structural barriers drive lack of access compared to high-income countries in which family and physician attitudes are identified as primary barriers. 9,10,14,22 In 2009, Lynch et al identified similar barriers to palliative care delivery in Eurasia such as limited access to specialists and stringent federal support, revealing a disappointing lack of regional progress over the past decade to increase the availability of palliative care services, particularly in childhood cancer care. 16 These results highlight the significance of structural barriers to palliative care integration in resource-limited settings and emphasize the importance of raising awareness and empowering local governments to support health care system infrastructure and increase hospital capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation